Foreign Language Education Policies in Iran: Pivotal Macro Considerations - Gholam Reza Kiany; Seyyed-Abdolhamid Mirhosseini; Hossein Navidinia (Journal of English Language Teaching and Learning, 2011)
Foreign Language Education Policy (FLEP) needs to be understood as part of broader educational policies and as situated within overarching social macro plans. In this paper, based on a conception of policy as distinct from goals and objectives, and with a view of the relevant literature, we will present some theoretical guidelines of setting and/or evaluating foreign language education policies in the context of broader social and educational policies. Considering theses guidelines a point of departure, several national plan-based documents and in some cases non-finalized documents that reflect some aspects of language education policies of Iran were examined to find the directions and orientations of these plans and the (in)consistencies among them: The 20-year National Vision; The Comprehensive Science Roadmap; The National Curriculum; Policies of the 5th 5-year Development Plan; The National Document of Education; Philosophy of Education in the Islamic Republic of Iran; Fundamental Principles in Islamic Education; and Roadmap of the Official and General Educational System. Referring to the strengths along with some shortcomings and inconsistencies among these documents as well as the statues of English in the so called global village, we call for a separate unitary FLEP document for Iran and present the requirements and procedure for its actualization.